2023
DOI: 10.3390/molecules28041802
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review on the Different Roles of Exosomes in TNBC and Exosomal-Mediated Delivery of microRNA/siRNA/lncRNA and Drug Targeting Signalling Pathways in Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer is the most potent metastatic type of breast cancer that can spread to other body parts. Chemotherapy and surgical intervention are the sole treatments for TNBC, owing to the scarcity of therapeutic targets. Manipulation of the membranes as per the desired targets of exosomes has recently gained much attention as a drug delivery method. Despite their known roles in different diseases, very few studies have focused on signalling that triggers the metastasis of triple-negative breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 126 publications
0
4
0
Order By: Relevance
“…TNBC usually has higher levels of apoptotic process ligand (PD-L1) expression than other subtypes of breast cancer. Keynote 522, Keynote 355, and others have shown that immune checkpoint inhibition in triple-negative breast cancer confers a survival benefit, and triple-negative breast cancer is currently the only type of breast cancer that has achieved clinical survival improvement in immunotherapy studies (Cortes et al, 2020;Schmid et al, 2020;Banerjee and Rajeswari, 2023).…”
Section: Nanoparticles For Immunotherapy Against Breast Cancer Lung M...mentioning
confidence: 99%
“…TNBC usually has higher levels of apoptotic process ligand (PD-L1) expression than other subtypes of breast cancer. Keynote 522, Keynote 355, and others have shown that immune checkpoint inhibition in triple-negative breast cancer confers a survival benefit, and triple-negative breast cancer is currently the only type of breast cancer that has achieved clinical survival improvement in immunotherapy studies (Cortes et al, 2020;Schmid et al, 2020;Banerjee and Rajeswari, 2023).…”
Section: Nanoparticles For Immunotherapy Against Breast Cancer Lung M...mentioning
confidence: 99%
“…SiRNAs directly induce the degradation of lncRNAs by recruiting the RNA-induced silencing complex (RISC) to interact with lncRNAs [ 157 ]. In lncRNA research, siRNAs have been effectively employed in various preclinical models to investigate the therapeutic potential of targeting specific lncRNAs [ 158 , 159 ]. For instance, the siRNA-mediated knockdown of lncRNA CASC9 significantly decreased tumor formation in an HCC mouse model [ 160 ].…”
Section: Targeting Strategies Of Lncrnas In Cancer Therapymentioning
confidence: 99%
“…MEK1 knockdown inhibited MAPK/ERK signalling, reversing the mesenchymal phenotype, reducing cell migration and invasion, and decreasing MMP-2/MMP-9 expression. Exosome-mediated delivery of anti-MEK1 siRNA effectively inhibited tumour growth, metastasis, and angiogenesis, suggesting potential for TNBC therapy [185]. Another study investigated RNA interference (RNAi) targeting the PIK3CA oncogene in breast cancer cells.…”
Section: Therapeutic Potential Of Evs In Breast Cancermentioning
confidence: 99%